2020
DOI: 10.1111/ppe.12665
|View full text |Cite
|
Sign up to set email alerts
|

Composite neonatal morbidity indicators using hospital discharge data: A systematic review

Abstract: Background: Neonatal morbidity is associated with lifelong impairments, but the absence of a consensual definition and the need for large data sets limit research. Objectives:To inform initiatives to define standard outcomes for research, we reviewed composite neonatal morbidity indicators derived from routine hospital discharge data. Data sources:PubMed (updated on October 12, 2018). The search algorithm was based on three components: "morbidity," "neonatal," and "hospital discharge data." Study selection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Multiple NMM often occur together and there has been considerable interest in using composite scores derived from multiple NMM. However, there has been no consistency in the implementation of composite outcomes and the general approach has, thus far, proven to be too heterogenous [21]. As an alternative, the current study could be followed up with a Bayesian approach in which NMM are modeled as a multivariate distribution and the correlations among the NMM are objectively estimated.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple NMM often occur together and there has been considerable interest in using composite scores derived from multiple NMM. However, there has been no consistency in the implementation of composite outcomes and the general approach has, thus far, proven to be too heterogenous [21]. As an alternative, the current study could be followed up with a Bayesian approach in which NMM are modeled as a multivariate distribution and the correlations among the NMM are objectively estimated.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review, comparing existing morbidity indicators based on International Classification of Diseases (ICD) diagnosis and procedure codes, showed that some were narrowly defined, covering only specific morbidities (i.e. respiratory complications) or focussed only on specific populations, such as very preterm births or uncomplicated term births 9 . In contrast, the Neonatal Adverse Outcome Indicator (NAOI), developed by Lain and colleagues using Australian data, aimed to cover all major severe neonatal morbidities and is intended to apply to the total population of viable live births 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Data GA, BW, gender, type of delivery, antenatal steroid administration, congenital disorders, and occurrence of all relevant obstetric information were collected ( 21 23 ). Apgar score at 5 min after birth, pH on cord blood, respiratory distress syndrome, occurrence of hypotension, feeding tolerance, and other gastrointestinal disorders were also prospectively recorded ( 22 , 24 , 25 ). Data on survival, morbidity, and duration of hospital stay were collected in a separate and codified data form.…”
Section: Methodsmentioning
confidence: 99%